Respuesta :

Answer:

1)· 5x + 2y = 9. First we solve for y. 2y= 9 -5x. y=(9-5x)/2. Now that we have the value of y. We substitute on the original equation and resolve. 5x + 2y = 95x + 2y = 9  5x + 2(9-5x)/2 = 9  5x + 9 - 5x = 9  9 = 9

That would be x = 1  

Now substitute and resolve to find y.  

5(1) + 2y = 9

5 + 2y = 9

2y = 4

y = 2

So our answer x=1 and y = 2. (1,2)

Proof :  

5(1) + 2(2) = 9

5+ 4 = 9

9 = 9

Step-by-step explanation:

hoped it helped for the first  one  i didnt now the second one